Microstructural and Mechanical Behaviour of Powder Metallurgy Processed TiC Reinforced Al7075-Based Composites - Crist Ting, May Yie (IRC, 2021)
Aluminium (Al) metal according to its strength to weight ratio have seized numerous attentions from all the research to further investigate and enhance its properties by adding reinforcement such as ceramic which have high hardness.